The metaverse: redefining the communicative paradigm through a critical discourse analysis of power and policy - Alaawad, Haitham Abdelrahman; Mohamed, Elsir Ali Saad; Abudraz, Ahd M. M.; Bashir, Bahaeldin Ali (Frontiers in Communication, 2026)
The metaverse presents a distinct policy challenge, effectively redefining communication, economics, and identity outside the bounds of current regulation. While corporate narratives emphasize decentralization and empowerment, they often obscure the consolidation of platform power, the replication of economic inequality, and the expansion of biometric surveillance. Using Critical Discourse Analysis, this study deconstructs these narratives to identify architectural control, digital gentrification, and the commodification of embodied identity as primary policy concerns. We propose actionable recommendations, including “fairness by design” audits, strict interoperability mandates to prevent monopolies, and the establishment of clear legal rights regarding biometric and embodiment data.